Standardized Beetroot Extract in Cardiovascular and Exercise Performance: A Randomized, Double Blind, Placebo Controlled, Crossover, Two Group, Two Periods, Clinical Study to Evaluate the Efficacy and Safety - Majeed, Muhammed; Majeed, Shaheen; Kiran Kumar Vuppala, Prachi Subhash Lad (International Journal of Innovative Research in Medical Science, 2017)
Increased plasma nitrate concentrations from dietary sources of nitrate have proven to benefit cardio vascular and exercise performance. Beetroot (BR) contains relatively high levels of nitrate (NO3), which increases nitric oxide storage. This study investigated whether dietary nitrate supplementation, in the form of a standardized beetroot extract formulation drink, could improve cardio vascular and exercise performance. Limited data is available regarding the effect of nitrate ingestion on cardio vascular and exercise performance, and limited studies have investigated the potential ergogenic effects of a small-volume, concentrated dose of beetroot juice. In a randomized double blind, placebo controlled, cross over, two groups, two periods design, 20 male healthy volunteers aged between 18-55 years were instructed to take one sachet per day (either Sabeet® (5.0 grams of Sabeet® sachet contains standardized beetroot extract with 2% nitrates) or Placebo before their daily exercise bout for a period of 14 days in Period I. After a washout period of 7 days, the treatment was crossed over for Period II, wherein subjects who received active product in period I received placebo in Period II which was again for 14 days. Present study demonstrates that dietary NO3-, administered in the form of beetroot juice, decreases systolic blood pressure (SBP) and improves cardiac output. These results may provide a mechanism by which nitrate exerts beneficial effects on muscle function with applications in sports performance.